Multilingualism and Its Impact of Islamic Boarding House Students in an Organized Multilingual Community - Ahmad Al Amin Putra (LITERA KULTURA : Journal of Literary and Cultural Studies, 2020)
This study was derived from multilingual issue where the informants were multilinguals. The gaps found in the previous study were the place and effects of multilingualism. The informants were gathered in one environment that organized with rules and limitations, the informants were not allowed to speak other languages except the language that ruled to use in certain areas, also, the informants originally came from various places and races which mean also different language, habit, and culture. This study was divided become threefold, multilingualism as a core point, language preference as an intermediate point and the effects of multilingualism as an advanced point. The advanced point involved informant’s personal identity and cultural value which adequately explained the multilingualism effect. This study used descriptive qualitative method, interview, and observation to gain the data. The data were in the form of a recording file from 3 informants. The results of the study were also splitted into 3 parts. First, the informants were language learners whose were proven as multilinguals. Second, formal and informal context were determined by boarding house rule and informant’s language choice such as speaking to teacher uses formal context and speaking in bedroom uses informal context. Third, the identity and culture from informant’s latest language affected the original identity and culture. In this case, Informants learnt English, the identity and culture of modernism influenced their original identity and culture, (e.g.) an informant prefered to be Singaporean rather than Javanese. Keywords : Islamic boarding house, multilingualism, identity, culture, language, one environment, rule, habit.